Anti-Roll Bar Optimization of an Urban Electric Bus - Alpar, Merve; Savran, Efe; Karpat, Fatih (Archives of Advanced Engineering Science, 2024)
Stiffness and stability are of high importance for vehicles. Existing suspension systems are working for vehicle stability increasing and they are not limited to own. One of the stability increaser extra elements is the anti-roll bar. The anti-roll bar is a suspension system supporter in vehicles. However, bar stiffness plays a critical role in vehicle stability. Bar stiffness can be managed on the predefined limitations. Therefore, a light, effective, and reliable vehicle system can be obtained. In this study, an urban electric bus anti-roll bar optimization was conducted numerically. For optimization, the bar diameter was changed between 25mm and 40mm. S235, 50CrV4, AISI 1065, and AL 7075 were selected for material comparison. According to vehicle stability limitations under the lateral 1 m/s2 acceleration, different bar diameters and material specifications were analyzed with the finite element method. Results of this study showed that the highest stiffness and the lightest bar can be achieved with a 36mm diameter and AISI 1065 steel combination. Obtained results can lead to vehicle stability studies in the future. Received: 8 December 2023 | Revised: 24 January 2024 | Accepted: 29 February 2024 Conflicts of Interest Fatih Karpat is the Editorial Board Member for Archives of Advanced Engineering Science, and was not involved in the editorial review or the decision to publish this article. The authors declare that they have no conflicts of interest to this work. Data Availability Statement Data sharing is not applicable to this article as no new data were created or analyzed in this study.